Effect of Bromelin Enzyme in Pineapple (Ananas comosus L.) on Caffeine Content and Flavour of Arabica Coffee - Arum, Ayu Puspita; Maulidana, Ach. Ariful; Patricia Sembiring, Susan Barbara; Savitri, Dyah Ayu (University of Jember, 2025)
Coffee is one of the main plantation commodities in Indonesia. One of the efforts to produce quality coffee is during the processing of the coffee. Quality coffee is coffee that has a bitter and sour flavour that is not excessive and has a low caffeine content. This is because high caffeine content is not good if consumed in excess. To reduce the caffeine content in coffee, you can use natural ingredients in the form of pineapple which contains the enzyme bromelain which is mixed during the fermentation process. The purpose of this research was to determine the effect of bromelain enzyme concentration and fermentation time on caffeine content and flavour in Arabica coffee. This study used a randomised complete factorial design. The first factor is the concentration of pineapple pulp, namely 0%, 40%, and 80%. The second factor was the length of fermentation time, namely 24 hours, 36 hours and 48 hours. Data were analysed using ANOVA analysis of variance if significantly different, then further tested by Duncan with a 5% error rate. The results showed that the interaction between the concentration of pineapple pulp and the length of fermentation had a very significant effect on the observation variable of caffeine content with the best results E2P1. The effect of pineapple pulp concentration had a significant effect on the pH parameter and a very significant effect on the caffeine content parameter. The effect of fermentation duration had a very significant effect on the observation variable of caffeine content.